2007
DOI: 10.2190/cs.9.2.f
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Hazards Models of Graduation

Abstract: Survival analysis is a statistical tool used to describe the duration between events. Many processes in medical research, engineering, and economics can be described using survival analysis techniques. This research involves studying engineering college student graduation using Cox proportional hazards models. Among male students with American College Test (ACT) scores only, those with better Science ACT scores were more likely to graduate. Among students submitting only Scholastic Assessment Test (SAT) scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…We believe that this is due to the strong academic support provided to student athletes at Georgia Tech through the athletic department. The finding related to Georgia residency makes sense: Students coming from other states and countries experience stronger selection effects than those attending from in-state (Chimka et al, 2008). Coming from geographically distant sites, they are likely to be more motivated and to have better academic preparation than students who are residents of Georgia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that this is due to the strong academic support provided to student athletes at Georgia Tech through the athletic department. The finding related to Georgia residency makes sense: Students coming from other states and countries experience stronger selection effects than those attending from in-state (Chimka et al, 2008). Coming from geographically distant sites, they are likely to be more motivated and to have better academic preparation than students who are residents of Georgia.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of gender, the evidence about persistence to graduation is mixed. Some have found that women are less likely to persist in engineering programs (Takahira, Goodings, & Byrnes, 1998; Zhang, Anderson, Ohland, & Thorndyke, 2004), whereas other research has found that women are more likely to graduate (Chimka, Reed-Rhoads, & Barker, 2008). …”
Section: Literature On Student Persistence To Graduationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that many engineering schools in Canada accept students based on their entrance averages, it makes sense that higher academic achievement in high school is correlated with higher retention rates [8] [34]. Although academic achievement is correlated with attrition, it cannot be considered a causal relationship.…”
Section: Academic Achievementmentioning
confidence: 99%
“…There are also specific measures from a student's high school academic record that have been found to correlate with attrition such as high school average and SAT math score [8] [12] [37] [48]. Also, good study and time management skills that students have from high school have been found to correlate with student success and retention [4].…”
Section: Academic Achievementmentioning
confidence: 99%